2020
DOI: 10.1039/c9ra10257d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, structure and up-conversion luminescence properties of novel cryolite K3YF6:Er3+, Yb3+

Abstract: Single-phase up-conversion luminescent materials K3YF6:Er3+, Yb3+ with cryolite structure were obtained for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 36 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…B ¼ Al 3+ , Sc 3+ , Ga 3+ , In 3+ , etc. ), 23 and up-conversion luminescent ion pairs can occupy the B site easily, forming a coupled isomorphic replacement in the cryolite crystal lattice. In recent years, research on cryolite structure compound as a luminescent host material has been widely reported, such as K 3 ScF 6 : Tm 3+ , Yb 3+ , 24 K 3 YF 6 : Er 3+ , Yb 3+ 23 , K 3 LuF 6 : Tb 3+ , Eu 3+ , 25 K 3 GaF 6 : Mn 4+ , 26 Na 3 GaF 6 : Eu 3+ , 27 K 3 GdF 6 , 28 K 3 AlF 6 : Mn 4+ .…”
Section: Introductionmentioning
confidence: 99%
“…B ¼ Al 3+ , Sc 3+ , Ga 3+ , In 3+ , etc. ), 23 and up-conversion luminescent ion pairs can occupy the B site easily, forming a coupled isomorphic replacement in the cryolite crystal lattice. In recent years, research on cryolite structure compound as a luminescent host material has been widely reported, such as K 3 ScF 6 : Tm 3+ , Yb 3+ , 24 K 3 YF 6 : Er 3+ , Yb 3+ 23 , K 3 LuF 6 : Tb 3+ , Eu 3+ , 25 K 3 GaF 6 : Mn 4+ , 26 Na 3 GaF 6 : Eu 3+ , 27 K 3 GdF 6 , 28 K 3 AlF 6 : Mn 4+ .…”
Section: Introductionmentioning
confidence: 99%